Indigenous Perspectives on Business Ethics and Business Law in British Columbia - Sorensen, Annette; van Dyk, Scott (Open textbook library., 2024)
This book explores business ethics and business law through the lens of Indigenous-settler relations in Canada (with a focus on British Columbia in particular). It aims to fill a gap in business curriculum and support instructors who want to bring Indigenous content into their classes. The book starts by exploring relevant history, focusing on treaties, legislation, and federal government policy. It then looks at business ethics and what it means for businesses to work ethically with Indigenous communities. And finally, the book discusses business law and the requirements and responsibilities for businesses doing work on Indigenous lands.